People power the Philippine experience. (GMA Radio Television News and Public Affairs, 1986)
A compact, comprehensive and moving documentary that tracts the roots of people power from the assasination of opposition party leader Benigno "Ninoy" Aquino to thr 4-day vigil at Camp Crame and Camp Aguinaldo in EDSA. Witnessed by the whole world, the four fateful days of February 22-25, 1986 changed the history of the Filipino nation.